2021
DOI: 10.3389/fbioe.2021.707208
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Black Phosphorus Nanosheet-Based Drug Delivery System for Targeted Photothermal-Chemo Cancer Therapy

Abstract: As a biodegradable material, black phosphorus (BP) has been considered as an efficient agent for cancer photothermal therapy. However, its systemic delivery faces several hurdles, including rapid degradation in blood circulation, quick clearance by the immune system, and low delivery sufficiency to the tumor site. Here, we developed a biomimetic nanoparticle platform for in vivo tumor-targeted delivery of BP nanosheets (BP NSs). Through a biomimetic strategy, BP NSs were utilized to coordinate with the active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Furthermore, studies have shown that they can selectively target cancer cells, slow treatment resistance, and minimize side effects [43,44]. In this regard, black phosphorus (BP) has also been emerging as a suitable nanomaterial that allows drug delivery and therapeutics in cancers [45]. Our in vivo findings underlined the miR205-5P-PEI-BP had an effective inhibition on tumorigenesis of TNBC cells and revealed the crucial therapeutic role of miR205-5p in TNBC and BP was a superior nonmaterial in delivery drug.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have shown that they can selectively target cancer cells, slow treatment resistance, and minimize side effects [43,44]. In this regard, black phosphorus (BP) has also been emerging as a suitable nanomaterial that allows drug delivery and therapeutics in cancers [45]. Our in vivo findings underlined the miR205-5P-PEI-BP had an effective inhibition on tumorigenesis of TNBC cells and revealed the crucial therapeutic role of miR205-5p in TNBC and BP was a superior nonmaterial in delivery drug.…”
Section: Discussionmentioning
confidence: 99%
“…Various photoresponsive NPs have been wrapped with different kinds of cell membranes to enable PTT of solidtumor cancers. This includes gold-based NPs (such as nanoshells, nanorods nanocages, nanostars, and nanodendrites) [40][41][42][43][44][45][46][47][48], polymeric NPs loaded with organic near-infrared (NIR) absorbing dyes (such as indocyanine green (ICG), IR780, IR820, and IR792) [49][50][51][52][53], Prussian blue NPs [54][55][56][57][58], non-gold metal-based NPs [59][60][61][62][63][64][65][66][67][68][69][70][71], liposomes [72][73][74], nanosheets (e.g., graphene-oxide, tungsten disulfide, and black phosphorous) [75][76][77][78], carrier-free systems made by co-assembling organic NIR dyes with other drugs [79][80][81], and other materials [82][83][84]…”
Section: Types Of Photothermally Active Np Cores Used In Biomimetic S...mentioning
confidence: 99%
“…Like platelets, mesenchymal stem cells (MSCs) have promise as biomimetic NP coatings due to their unique migration and tumor tropism, which are mediated in part by surface receptors on their plasma membranes [77]. Source-related advantages of MSCs include their ease of isolation from in vitro cell culture and potential to be extracted from diverse tissues (i.e.…”
Section: Membrane Types Used To Wrap Phototherapeutic Npsmentioning
confidence: 99%
See 2 more Smart Citations